Prognostic impact of hypochromic erythrocytes in patients with pulmonary arterial hypertension - Xanthouli, Panagiota; Theobald, Vivienne; Benjamin, Nicola; Marra, Alberto M.; D’Agostino, Anna; Egenlauf, Benjamin; Shaukat, Memoona; Ding, Cao; Cittadini, Antonio; Bossone, Eduardo; Kögler, Maria; Grünig, Ekkehard; et al. (Respiratory research, 2021)
Iron deficiency affects up to 50% of patients with pulmonary arterial hypertension (PAH) but iron markers such as ferritin and serum iron are confounded by several non-disease related factors like acute inflammation and diet. The aim of this study was to identify a new marker for iron deficiency and clinical outcome in PAH patients.
Gesehen am 13.12.2021